Identifikasi Perawatan Ortodontik Spesialistik dan Umum - Ardhana, Wayan (Majalah Kedokteran Gigi Indonesia, 2013)
The goal of orthodontic treatment is to improve the arrangement of teeth, with a good occlusal contact, so as to achieve an efficient occlusion function, a pleasant and aesthetical facial appearance and long-term stability after the treatment. To achieve these goals, a dentist with his capability and competence must be able to identify the malocclusion cases. The purpose of this library research is to discuss the case of malocclusion based on dentoskeletal components that form the malocclusion, to establish care and orthodontic appliance that can be used, to identify the level of difficulty of care, and to gain an understanding of capabilities and limitations in fulfilling the purpose of the treatment in order to avoid any problems in the future for both patients and physicians.